An evaluation of the British standard proposals for symbols on machine tool indicator plates - Easterby, R. S. (College of Aeronautics, 1965)
The work detailed in this report has been undertaken as part of a research project supported by the Machine Tool Industry Research Association on Ergonomics and Machine Tool Design. In an early research project report, some comments were offered on the Draft British Standard for Symbols for Machine Tool Indicator Plates, and the Director of M.T.I.R.A, invited the author to elaborate on these preliminary criticisms. Although finalisation of the British Standard was imminent, it was realised that it would be remiss if a research project specifically devoted to ergonomics and machine tool design did not make a detailed and constructive assessment of the proposed standard symbols.